The pollinators : agents for life [videorecording (DVD)] - Jones, Andy T.; Nahikian, Jess (Dreamscape explore., 2025)
With a single touch, a brief pause on a petal, these tiny creatures maintain balance on our planet. Imagine a world where the vibrant hum of bees, the silent flutter of butterflies, and the midnight dance of bats all fall quiet. This documentary, The Pollinator-Agents for Life, takes viewers on an intimate journey into the lives of Earth's unsung heroes. Through sweeping cinematography and microscopic vistas, we witness the delicate balance these creatures maintain in nature, from the honeybee working tirelessly in sunlit meadows to the tiny, lesser-known pollinators, like beetles and moths, who play their part under the stars. The film explores the fascinating diversity of pollinators -- from the dazzling patterns of tropical hummingbirds hovering over wild blooms to desert bats that pollinate agave. Every scene reveals their intricate relationship with plants -- where a single touch, a brief pause on a petal, ensures the continuation of life on our planet. But this film is more than a celebration of nature's beauty. As we delve deeper, a darker shadow emerges. The impacts of climate change, pesticides, and habitat loss are causing pollinator populations to plummet. The film draws startling connections between the disappearance of these creatures and the collapse of entire ecosystems, threatening food sources, biodiversity, and even human beings. With its soaring visuals and compelling narrative, The Pollinators, Agents for Life serves as both a tribute to the wonders of nature and a call to action, reminding us of what is at stake if we allow these creatures to disappear.--Container.